ANALISIS POTENSI DAN PENGELOLAAN PERIKANAN DALAM PERSPEKTIF KETAHANAN PANGAN DI WILAYAH PESISIR KABUPATEN LAMPUNG BARAT - Nazdan Nazdan; Budi Setiawan; Dadang Sukandar (Food and Nutrition Society of Indonesia, 2008)
The aim of this study was to analyze the potential resources and management of fisheries during the periods of 2003–2007 at the coastal zone of West Lampung. Primary and secondary data was analyzed using SWOT. SWOT analysis is a technique used to identify various factors systematically in order to formulate a management strategy. The result showed that the total score for internal factor (strengths-weaknesses) was 0.23 and the total score for external factor was -0.32 (opportunities-threats); which placed the fisheries management at the coastal zone of West Lampung regency in the second quadrant position. The priority of alternative strategy carried out for optimum and sustainable fisheries management was to develop aquaculture (fresh water and estuary), to resolve conflicts of interest on natural resources used at the coastal zone of West Lampung, and to improve the involvement of formal and non formal institutions in implementing environment friendly efforts as well as in resolving environmental degradation problems.